If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x = 27 + -2x Solving x = 27 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. x + 2x = 27 + -2x + 2x Combine like terms: x + 2x = 3x 3x = 27 + -2x + 2x Combine like terms: -2x + 2x = 0 3x = 27 + 0 3x = 27 Divide each side by '3'. x = 9 Simplifying x = 9
| x-10/x+2=7 | | -2.7=-1.3+0.7x | | x-(8x^(1/2))+4=0 | | 8/11(n+10)=64 | | -3x+12=9 | | 9-y=9 | | 15x-45+3x=18x+18-13 | | x+0.07x=16.05 | | 9x-1=8x+19 | | (9x+2)/5=4 | | (3x^2+2x-9)-(-3x+4)= | | -3-y=9 | | (3y/2a)/(8a^2y5/15y) | | 6x^2+2x-58=0 | | 2.3x-9.34=6.3 | | 4/17(x)=20 | | 3x-14=2x+19 | | -40-3x=14-10x | | 3-2(1/7) | | 8c+c=27 | | -4y-2+3y+4=-5 | | 24w^9x^6y-22x^4y^6= | | 2(1/7) | | 1x-6=3x-4 | | -[4(7)+2]-[3(7)-4]=x | | 4b+29=48 | | -[4(7)+2]-[3(7)-4]=-5 | | 3-21/7 | | y=3x+6graph | | 60=-5x+9 | | -(4y+2)-(-3y-4)=-5 | | 4+4y=8 |